Your heart and how it works - Zim, Herbert Spencer 1909-; Schrotter, Gustav ([New York] W. Morrow, 1959)
Presents the development of the heart to the four-chambered heart of a mammal, heart muscle, various aspects of its beat, blood pressure, the valves of the heart, and diseases and defects which can affect this all-important organ.
Keywords: Heart -- Juvenile literature; Heart